Frequency of Hypoalbuminemia in Acute Ischemic Stroke Patients Presenting at Tertiary Care Hospital, Karachi: Frequency of Hypoalbuminemia in Acute Ischemic Stroke - Aman, Habiba; Zakir, Humaira; Naz, Bukhtawar; Khokar, Amanullah; Manzoor, Waqas; Haque, Nadeem Ul (Pakistan Journal of Health Sciences, 2025)
Stroke is regarded as the second most commonly reported death worldwide. The effect of albumin is mainly in the early reperfusion phase of acute ischemic stroke. Objective: To determine the frequency of hypoalbuminemia in patients with acute ischemic stroke. Methods: This cross-sectional observational study was carried out for six months (from April 2024 to October 2024) at the Department of Medicine, Al-Tibri Medical College, Karachi. 196 patients newly diagnosed with stroke patients presented within 24 hours were included, while patients with renal impairment, liver disease, etc., were excluded. SPSS version 24.0 was used for data analysis. Demographical data were reported with post-stratification chi-square applied, keeping p-value<0.05 as statistically significant. Results: A total of 196 patients with acute ischemic stroke were included in this study. The mean age in our study was 44.14 ± 4.49 years. 146 (74.5%) were male and 50 (25.5%) were female. Out of 196 acute ischemic stroke patients, 90 (45.9%) and 106 (54.1%) had and did not have hypoalbuminemia. Conclusions: It was concluded that a significant frequency of hypoalbuminemia was observed among patients presenting with acute ischemic stroke. However, association with stroke severity could not be established. Therefore, patients presenting with ischemic stroke ought to be screened for serum albumin levels when presenting to the hospital. In addition, patients with low serum albumin levels must be considered high risk and should be managed accordingly.